ФЕНОМЕНИ ГЛОБАЛІЗМУ ТА АНТИГЛОБАЛІЗМУ В КОНТЕКСТІ ФІЛОСОФСЬКОГО ОСМИСЛЕННЯ МИСТЕЦТВА АВАНГАРДИЗМУ ТА СЮРРЕАЛІЗМУ - Культенко, В. П. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
Стаття пропонує аналіз філософських позицій таких апологетів авангардизму та сюрреалізму, як Г. Маркузе, Т. Адорно, В. Беньямін в контексті осмислення можливостей впливу культури на реалії життя людини у сьогоднішньому світі, що перебуває під впливом двох різноспрямованих рухів – глобалізації та антиглобалізму. Культенко В.П. Феномены глобализма и антизлобализма в контексте философского осмысления искусства авангардизма и сюрреализма. Статья предлагает анализ философских позиций таких апологетов авангардизма и сюрреализма, как Г. Маркузе, Т. Адорно, В. Беньямин в контексте осмысления возможностей влияния культуры на реалии жизни человека в сегодняшнем мире, который пребывает под воздействием двух разнонаправленных тенденций – глобализации и антиглобализма. Ключевые слова: глобализм, антиглобализм, авангардизм, сюрреализм, культурная политика. Kultenko V.P. Phenomena of globalization and anti globalization at the context of philosophical understanding of avangardism and surrealism art. The analysis of philosophic positions of such apologists of avangardism and surrealism as G. Marcuse, T. Adorno, V. Benjamin is proposed in the article. The analysis is undertaken in the context of understanding of possibilities of cultural influence on human life in modern world which is under the impact of two opposite tendencies of globalization and anti globalization. Keywords: globalization, antiglobalization, avangardism and surrealism art, cultural politic.